PERAN DELEGASI FA. APONNO DALAM DEMOBILISASI EKS KNIL AMBON TAHUN 1949-1951 - Mahetsa, Ranu Yolan Eky; Nugraha, Fajar Muhammad, FMN (Multikultura, 2026)
The dissolution of the Koninklijk Nederlands-Indisch Leger (KNIL) following the recognition of Indonesian sovereignty created serious problems for KNIL soldiers from Ambon, particularly with regard to their legal status, security, and place of demobilization. The unstable political and security situation in Eastern Indonesia in the early 1950s, combined with tensions between the Netherlands and the Republik Indonesia Serikat, further intensified the uncertainty surrounding the fate of former Ambonese KNIL soldiers. It was within this context that the Aponno Delegation emerged as a representative body advocating the interests of former Ambonese KNIL members who rejected demobilization within the territory of the Republic of the United States of Indonesia. This study aims to analyze the role and strategies of the Aponno Delegation in opposing the planned relocation of former Ambonese KNIL soldiers to the territory of the Republic of the United States of Indonesia and in advocating for their demobilization rights during the period 1950–1951. The research data were obtained from primary sources in the form of archival legal petitions submitted by the Aponno Delegation to the Dutch government, preserved at the Nationaal Archief, the Staatsblad van het Koninkrijk der Nederlanden, and reports from Dutch-language newspapers accessed through Delpher. Secondary sources, including books and scholarly articles, were used to strengthen the historical context and analysis. This research employs the historical method, encompassing the stages of heuristics, source criticism, interpretation, and historiography. External and internal criticism were conducted to assess the authenticity and credibility of the sources, after which the data were interpreted chronologically and contextually. The findings indicate that the Aponno Delegation played a significant role in the demobilization process of former Ambonese KNIL soldiers, particularly through legal and political strategies that influenced the policy leading to their transfer to the Netherlands in 1951